Aspek Gramatikal dan Leksikal Lirik Lagu Gala Bunga Matahari Karya Sal Priadi - Nurhaliza, Julia Najma; Wahyono, Hari (Kajian Bahasa dan Sastra (KABASTRA), 2025)
The aim of the research carried out was to analyze the grammatical and lexical structure used in the lyrics of the song "Gala Bunga Matahari" by Sal Priadi. This analysis focuses on identifying sentence patterns, verb use, and other linguistic elements that shape the message and aesthetics of the song's lyrics. This research uses a qualitative method with a descriptive approach, where song lyrics are analyzed based on grammatical and linguistic theories. The research results show that the song "Gala Bunga Matahari" uses a variety of complex sentence structures, emotional word choices, and deep language style to convey themes of sadness and longing. It is hoped that this analysis can provide a role in in-depth understanding of how grammatical structure can influence the interpretation and appreciation of a song.